Ishita Banerjee Dube. Divine Affairs: Religion, Pilgrimage, and the State in Colonial and Postcolonial India. Shimla: Indian Institute of Advanced Study, 2001. 195 pp. - Lorenzen, David N (Estudios de Asia y África, 2004)
-